Unmanned Aerial Vehicle for Transmission Line Inspection: Status, Standardization, and Perspectives - Li, Xin; Li, Zijian; Wang, Haizhi; Li, Wanlin (Frontiers in Energy Research, 2021)
As the biggest country of power consumption and generation, China owns the largest scale of transmission line worldwide. The application of unmanned aerial vehicle (UAV) in inspection has been carried out for many years in China because of its strong adaptability and safety compared to the traditional manual way. For the further development of UAV application technology in transmission line inspection, China has accumulated rich experiences and greatly improved line inspection efficiency, and formed a relatively complete UAV transmission line inspection standardization system including operation safety management, equipment configuration method, functional quality requirements, etc. However, there still exists some obstacles that need to be tackled due to the fact that China’s UAV transmission line inspection standardization and its international promotion have not been thoroughly and comprehensively studied at present. Based on an in-depth analysis of current China’s UAV transmission line inspection standardization, this paper employs SWOT-PEST analysis to insightfully investigate international promotion opportunities/challenges under the current situation, upon which several constructive suggestions are proposed from four aspects of politics, economy, society, and technology. The ultimate purpose is to design feasible schemes to boost the international promotion of China’s UAV transmission line inspection standardization and further development of international UAV inspection technology.